Changing perspectives: alternative border realities - Haferkamp, Barne; Sandman, Karl (My University, 2022)
Till’s (2009) statement “Architecture is political. Full Stop.” (p.124), lays down the theoretical groundwork for this thesis. Challenging the proclaimed political inability of architectural practice, this work takes a strong political positioning against the current deterrent migration politics of the European Union (hereinafter EU) and the agency of architecture within. This thesis explores a design approach which enables a speculative visualisation of the discussed social political spectrum of alternative EU external land border realities. It opposes the spatial dimensions of the current border reality, to these defined alternatives with a focus on migration perspectives. The right to asylum is protected by international and European legislation. Nevertheless, border countries’ national sovereignty is instrumentalized against migrants and their rights to prevent them from reaching the EU’s territory. This manifests in inhumane fortifications along the border lines and even leads to illegal ‘push backs’. A fortified EU effectively denies refugees their right to seek asylum which results in irregular migration with high fatality rates. The current situation violates the Charter of Fundamental Rights of the EU and must be confronted beyond the political discourse. Amongst others, the legislative opposition, consulting political foundations and human rights organisations are pushing for a paradigm shift in EU migration politics. Assorting migration as inevitable, they develop sustainable strategies for a humane approach. Facing this societal challenge, architects and urban designers must finally commit to their social responsibility, being the ones planning the very spaces which directly or indirectly cause harm and death for migrants. This thesis portrays multiple perspectives on migration politics out of a spatial point of view. The first chapter seeks to analyse and visually portray the current inhumane border situation, through detailed mapping of ‘Fortress Europe’ down to its constructional elements. The second chapter depicts spatial interpretations of alternative realities, based on varying perspectives in the internal social political spectrum and stakeholders with external migration experience. These visions are developed through graphical transcription of interviews with relevant people to ensure that the outcome reflects the views of affected social groups. By contrasting the reality to its alternatives, this thesis aims to provoke discussions around the role of the architect in the challenging of current EU migration politics. Therefore this work becomes a discursive object in itself.
Keywords: Political Architecture, Speculative Design, Alternative RealityEuropean Borders, Migration